Homoeriodictyol, targeting the bitter taste receptor TAS2R14, lowers the secretion of pro-inflammatory chemokines upon treatment with SARS-CoV-2 peptide pools in human peripheral blood mononuclear cells - Danzer, Barbara; Andersen, Gaby; Kahlenberg, Kristin; Somoza, Veronika (Frontiers in Immunology, 2026)
Excessive cytokine production is a major complication in severe COVID-19. Treatment with antiviral drugs often elicits a bitter taste through activation of bitter taste receptors (TAS2Rs). Since ectopically expressed TAS2Rs can alter cytokine secretion, we hypothesized that homoeriodictyol (HED), a broad TAS2R ligand, modulates the cytokine response to SARS-CoV-2 peptide pools (PP) in human peripheral blood mononuclear cells (PBMCs). Treatment of PBMCs isolated from healthy donors with PP for 24 h induced the mRNA expression of CXCL9, CCL7, and CCL2, the most of 116 cytokines tested. Protein release of these chemokines was quantified by ELISA after PP treatment for 3, 6, 12, 24, and 48 h. The results identified 24 h as the optimal incubation time to distinguish PP-induced chemokine release among PBMCs, T–cells, and T–cell–depleted PBMCs. PBMCs demonstrated the highest mean fold changes of CXCL9, CCL7, and CCL2 with 12, 52, and 96, respectively. Involvement of TAS2Rs was verified (i) by co-incubation of the PBMCs with PP and HED, which decreased (p<0.01) the PP-induced secretion of CXCL9, CCL7, and CCL2 by a mean of 80%, 96%, and 95%, respectively, and (ii) via an siRNA knock-down approach targeting TAS2R14. TAS2R14 knock-down increased (p<0.05) the CXCL9, CCL7, and CCL2 release after 24 h of PP incubation by 33%, 34%, and 29%, respectively. These results reveal TAS2Rs on human PBMCs being functionally active in the chemokine immune response to SARS-CoV-2-specific peptides, with the broadly tuned TAS2R14 as a promising target for anti-inflammatory immune system regulation in viral infections.